THE DIRECT LATERAL APPROACH TO THE DISTAL TIBIA AND FIBULA: A SINGLE INCISION TECHNIQUE FOR DISTAL TIBIAL AND PILON FRACTURES - Femino, John E. (The University of Iowa, 2009)
Distal tibia fractures remain difficult injuries to treat when fracture displacement precludes non-operative treatment. Different methods of treatment including limited internal fixation with external fixation, as well as open reduction and internal fixation have been recommended. Open reduction and internal fixation is often favored for the improved ability to anatomically reduce displaced fractures, particularly articular fractures. However, wound complications due to the associated trauma to the fragile soft tissue envelope in this region continue to be a significant concern. The authors present a surgical approach for open reduction and fixation of distal tibia and fibula fractures through a single lateral incision, which respects the angiosomes of the distal leg and ankle. This can, in some cases, resolve the need to delay ORIF of the tibia since the incision is essentially the same as that used for the immediate ORIF of fibula fractures, which is commonly used in the staged treatment of distal tibial and plafond fractures. This approach can be extended proximally and distally to allow treatment of other injuries about the ankle and hindfoot. Illustrative cases are provided.